2014
DOI: 10.1371/journal.pone.0101070
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical and Cellular Evidence Demonstrating AKT-1 as a Binding Partner for Resveratrol Targeting Protein NQO2

Abstract: BackgroundAKT plays an important role in the control of cell proliferation and survival. Aberrant activation of AKT frequently occurs in human cancers making it an attractive drug targets and leading to the synthesis of numerous AKT inhibitors as therapeutic candidates. Less is known regarding proteins that control AKT. We recently reported that quinone reductase 2 (NQO2) inhibited AKT activity, by unknown mechanisms.Methodology/Principal FindingsIn this study, molecular modeling was used to query interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Protein kinase C interacts with the PH domain of Bruton tyrosine kinase (BTK) and inhibits BTK activity (Yao, Kawakami, & Kawakami, 1994). One group has reported that N‐ribosyldihydronicotinamide:quinone reductase 2 (NQO2), an oxidoreductive enzyme, interacts with AKT via the PH domain of AKT to inhibit AKT activity (Hsieh et al, 2014). Here, we showed that TXNIP interacts with AKT via the PH domain of AKT and inhibits the kinase activity of AKT (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinase C interacts with the PH domain of Bruton tyrosine kinase (BTK) and inhibits BTK activity (Yao, Kawakami, & Kawakami, 1994). One group has reported that N‐ribosyldihydronicotinamide:quinone reductase 2 (NQO2), an oxidoreductive enzyme, interacts with AKT via the PH domain of AKT to inhibit AKT activity (Hsieh et al, 2014). Here, we showed that TXNIP interacts with AKT via the PH domain of AKT and inhibits the kinase activity of AKT (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…AKT is a serine–threonine kinase that is involved in a variety of cellular processes including cell survival, proliferation, and metabolism (Hsieh, Lin, Bennett, Wu, & Wu, 2014). AKT has a structure consisting of an N‐terminal pleckstrin homology (PH) domain, a kinase domain (KD), and a C‐terminal hydrophobic regulatory region (HM) (Parikh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Asian men, incidence of prostate cancer among men is also significantly low in France which is due, a significant part, to a large intake of red wine, a natural source of resveratrol, leading to the concept of “French Paradox.” Work from our laboratories have focused for many years on the molecular mechanisms of androgen independence and bone metastasis in prostate cancer, with particular reference to the use of curcumin (used in Asian cuisine) and resveratrol (found in red wine) as significant anti‐inflammatory, anti‐oxidative agents, and as nutritional modulators of cancer progression . Our earlier work on the mechanisms of androgen independence in prostate cancer cells has led to a better understanding of the function of the enzyme NRH: quinone oxidoreductase (NQO2) in prostate carcinogenesis . In this communication, the role of the enzyme NQO2 is investigated further with respect to its role not only in regulating oxidative stress but also in regulating prostate cancer metastasis and how glutamine metabolism influences all these processes.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Our earlier work on the mechanisms of androgen independence in prostate cancer cells has led to a better understanding of the function of the enzyme NRH: quinone oxidoreductase (NQO2) in prostate carcinogenesis. 25,26 In this communication, the role of the enzyme NQO2 is investigated further with respect to its role not only in regulating oxidative stress but also in regulating prostate cancer metastasis and how glutamine metabolism influences all these processes. Our results highly suggest a heretofore uninvestigated role for the enzyme NQO2 in the genesis and function of large extracellular vesicles (LEVs), particularly in the modulation of the bony microenvironment in advanced prostate cancer through its specific interaction with caveolin-1 which is implicated in the genesis of hormone refractory and metastatic prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many naturally occurring compounds such as resveratrol (RES), flavopiridol (FLAV), and piperlongumine (PIP) are multimechanistic compounds that have been identified as putative chemotherapeutics (Pan et al, 2012). Treatment with RES has been shown to cause increases in cytosolic calcium (Ma et al, 2007;Peterson et al, 2016), bind to various proteins to induce intrinsic apoptosis (Locatelli et al, 2005;Calamini et al, 2010;Hsieh et al, 2014), and cause production of ROS (Miki et al, 2012). FLAV inhibits cyclin dependent kinases to disrupt the cell cycle and causes production of ROS (Gupta et al, 2010;Shao et al, 2016), whereas PIP has been shown to cause ROS production and inhibit signal transducer and activator of transcription 3 and nuclear factor kappa-light-chain-enhancer of activated B cells (Kong et al, 2008;Adams et al, 2012;Ginzburg et al, 2014;Gong et al, 2014;Bharadwaj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%